2014
DOI: 10.1590/1983-1447.2014.02.43715
|View full text |Cite
|
Sign up to set email alerts
|

Stimulus-response time to invasive blood pressure alarms: implications for the safety of critical-care patients

Abstract: Observational, descriptive, exploratory, case study with the objective of measuring the stimulus-response time of the team to alarms monitoring invasive blood pressure (IBP) and analyzing the implications of this time for the safety of the patient From January to March 2013, 60 hours of structured observation were conducted with registration of the alarms activated by IBP monitors in an adult ICU at a military hospital in the city of Rio de Janeiro. 76 IBP alarms were recorded (1.26 alarms/hour), 21 of which (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 8 publications
(19 reference statements)
1
10
0
Order By: Relevance
“…Characteristics of included studies are shown in Table . Of the 24 observational studies, 15 included adult patients, 7 included pediatric patients, and 2 included both adult and pediatric patients . All were single‐hospital studies, except for 1 study by Chambrin and colleagues that included 5 sites.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Characteristics of included studies are shown in Table . Of the 24 observational studies, 15 included adult patients, 7 included pediatric patients, and 2 included both adult and pediatric patients . All were single‐hospital studies, except for 1 study by Chambrin and colleagues that included 5 sites.…”
Section: Resultsmentioning
confidence: 99%
“…The number of patient‐hours examined in each study ranged from 60 to 113,880 . Hospital settings included ICUs (n = 16), general wards (n = 5), EDs (n = 2), postanesthesia care unit (PACU) (n = 1), and cardiac care unit (CCU) (n = 1) . Studies varied in the type of physiologic signals recorded and data collection methods, ranging from direct observation by a nurse who was simultaneously caring for patients to video recording with expert review .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The remaining 55 alarms were defined as fatigued by the authors, because they sounded for more than 10 minutes without response from profissionais. 24 Therefore, with regard to violations, understanding the social context is important to understand motivations that led to the violation behavior. This calls attention to organizational culture and the behavior of those who are involved.…”
Section: Discussionmentioning
confidence: 99%
“…Many of these alarms are considered false, with no clinical meaning, and contribute to alarm fatigue, the desensitization of the team for important clinical alarms manifested in behaviors such as ignoring them, silencing them, turning them off or turning down their volume. This scenario has raised the interest of researchers to measure the time between stimulus and response of ICU professionals to equipment alarms (25)(26) .…”
Section: Discussionmentioning
confidence: 99%